Biological profiling of piperazinediones for the management of anxiety - Kumar D.; Gupta S.K.; Ganeshpurkar A.; Singh R.; Kumar D.; Das N.; Krishnamurthy S.; Singh S.K. (My University, 2025)
The anxiolytic effect of earlier reported piperazinediones was assessed by elevated plus maze (EPM), hole-board and open-field (OFT) tests. The rats were administered pretreatment of three different doses i.e. 2, 1 and 0.5 mg/kg of compounds 52, 53 and 55 for seven consecutive days. Compound 52 and diazepam showed increase in open arm entries, increase in time spent therein and total arm entries at 1 mg/kg dose. The compound also produced increase in the number of head dip, sniffing behavior and total number of squares crossed compared to diazepam. In OFT paradigm grooming behavior, number of central squares crossed and the time spent in central area did not reveal statistical differences for diazepam and compound 52 at 1 mg/kg dose. Flumazenil mediated antagonism experiments of these showed that they were acting through benzodiazepine site on GABAA receptor. The levels of 5HT and 5HIAA were estimated in amygdalar region. Level of 5HT was found to be equivalent in case of compound 52 and diazepam treatment at dose of 1 mg/kg. Interestingly, compound 52 did not display sedative effect at higher dose in both animal models. Thus, present study indicated that compound 52 produced anti-anxiety property through modulation of GABAergic transmission. © 2018 Elsevier Inc.